2006
DOI: 10.1097/01.aids.0000198087.47454.e1
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors of HIV-infected patients with HCV-related end-stage liver disease

Abstract: Ninety-five (62%) patients died during the follow-up. In 79 (85%) individuals, the cause of death was liver related. The median survival time was 13 months. Independent predictors of survival were Child score [hazard ratio (HR), 1.2; 95% confidence interval (CI), 1.08-1.37; P = 0.001], CD4+ cell count at decompensation lower than 100 cells/microl (HR, 2.48; 95% CI, 1.52-4.06; P < 0.001) and hepatic encephalopathy as the first hepatic decompensation (HR, 2.45; 95% CI, 1.41-4.27; P = 0.001). HAART was prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
117
2
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 21 publications
13
117
2
2
Order By: Relevance
“…25 The impact of immunosuppression on liver mortality is one reason for this recommendation. [2][3][4][5] In the present study, lack of control of HIV replication was a risk factor for progression. This is an additional reason to consider earlier ART initiation.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…25 The impact of immunosuppression on liver mortality is one reason for this recommendation. [2][3][4][5] In the present study, lack of control of HIV replication was a risk factor for progression. This is an additional reason to consider earlier ART initiation.…”
Section: Discussionmentioning
confidence: 49%
“…One of the cohorts was a collaboration of 11 centers, and the other cohort recruited patients from five centers from January 1997. 4,5 All individuals were evaluated at clinical visits scheduled every 3 months. Nine university hospitals participating in these cohorts followed 9,257 HIV/HCV-coinfected individuals from January 1986 to January 2008.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In HIV-infected patients, the predictors of mortality after the first episode of decompensation include a high Child-Pugh score and hepatic encephalopathy as the presenting feature. 11 The manifestations of ESLD appear to be similar to those in HIV-negative patients, and survival after the first episode of decompensation is markedly reduced. 12 …”
Section: Increasing Burden Of Liver Diseasementioning
confidence: 96%
“…Liver disease caused by HIV-1/HCV coinfection is characterized by increased liver fibrosis and cirrhosis. Several groups have observed that fibrosis progresses more rapidly in patient coinfected with HIV-1 and HCV (Gonzalez et al, 2003) and HCC develops more frequently and more quickly in HIVinfected individuals with HCV in comparison to HCV monoinfected patients Kramer et al, 2005;Merchante et al, 2006;Pineda et al, 2005). Recent screening studies have utilized known serum markers identified in HCV-infected patients to evaluate the progression of liver disease (Imbert-Bismut F, 2001;Rosenberg et al, 2004;Sumida et al, 2000;Suzman et al, 2008) and have shown correlation between elevated serum concentrations of alpha feto protein (AFP) and the occurrence of HCC (Chen et al, 1984) in coinfected patients.…”
Section: Introductionmentioning
confidence: 99%